The correlation between vascular endothelial growth factor and prostate cancer with and without metabolic syndrome - Zhou, Ya-nan; Song, Jin-qi; Tu, Gang-liang; Xu, Hui; Ding, Meng (Nepalese Journal of Cancer, 2021)
Objective: To investigate the relationship between vascular endothelial growth factor (VEGF), metabolic syndrome and its components and degree of differentiation of prostate cancer. Methods: The clinical data of 49 PCa cases treated during October, 2018 to February, 2021 were retrospectively analyzed, including patients’ height, weight, body mass index (BMI), age, blood pressure (BP), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), fasting blood glucose (FBG), vascular endothelial growth factor (VEGF) and Gleason score. Results: Compared with simple PCa group, BMI, the MS group had higher BMI, diastolic blood pressure (DBP, FGB, TG) and VEGF (P<0.05), and higher Gleason score (P<0.05). MS group had a higher degree of malignancy (Gleason≥8). Conclusion: This suggests that MS may promote the progression of PCa, and the increase of VEGF level can indicate the presence of MS in PCa patients, reflecting the progression of PCa to a certain extent.